"Our International Journal": UN Publications and Soviet Internationalism after Stalin. Issue 4 (3rd September 2021) - PORTER, LOUIS H.
Abstract : This article explores the role of the United Nations (UN) in the post‐Stalin Soviet internationalist imagination. It analyzes letters that Soviet readers wrote to the editorship of The UNESCO Courier, a monthly magazine translated into the world's major languages and released to a global readership by the United Nations Educational, Scientific, and Cultural Organization (UNESCO). I illustrate how a small but devoted group of Soviet readers received the magazine's message, and how this message commingled for these readers with Soviet internationalist values and practices. The Courier not only featured international news on education, science, and culture, but also acted as a public‐relations arm of UNESCO, promoting ideas of world governance, world civic duty, and international community at the heart of the UN project. The magazine's "Letters‐to‐the‐Editor" section became a platform where Soviet readers articulated their own visions for internationalist solidarity and action inspired by the ideas promoted in the magazine. Hatched by a unique group of Soviet "one‐worlders" whose embrace of the UN and Soviet loyalty coexisted, these remarkably creative visions reveal the existence in the USSR of grassroots support for the UN's brand of world governance and the world body's function as a vehicle for Soviet internationalist expression.